Pengaruh Pemberian Pupuk Kompos Ampas Kelapa dan Air Laut terhadap Pertumbuhan Tanaman Selada (Lactuca Sativa L.) - Nur Fadillah Pulukadang; Akram La Kilo; La Ode Aman; Astin Lukum; Erni Mohamad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of coconut pulp and seawater compost on the growth of lettuce (Lactuca Sativa L). This type of research uses a quantitative method. Based on the results of the study, the treatment of coconut pulp and seawater compost on the most optimal plant height is the treatment on the 28th day because there is the greatest potential difference in treatment compared to other days and the treatment of coconut pulp and seawater compost on the optimal number of leaves is the treatment on the 42nd day, especially in treatment 5 which produces the highest number of leaves.